RGDV peptide selectively inhibits platelet-dependent thrombus formation in vivo. Studies using a baboon model. - Cadroy, Y (1989)
Since platelet hemostatic functions are mediated in part through the binding of adhesive proteins containing an RGD (Arg-Gly-Asp) recognition sequence, and since platelet reactions may be inhibited in vitro by RGD-containing peptides, we assessed in vivo the antithrombotic activity of RGDV (Arg-Gly-Asp-Val) tetrapeptide using a baboon thrombosis model. Thrombus formation was induced by a device consisting of a tubular segment coated with type I collagen, followed by two regions of expanded diameter exhibiting disturbed flow and stasis. The thrombogenic device was incorporated into femoral arteriovenous shunts under conditions of intermediate wall shear rate (100 s-1). Thrombus formation was measured by scintillation camera imaging of 111In-platelets and by counting of 125I-fibrinogen/fibrin. Thrombus that formed on the collagen substrate was rich in platelets, while thrombus formed in the disturbed flow regions was rich in fibrin and red cells. RGDV peptide was infused proximal to the thrombogenic device to maintain local plasma concentrations of 25, 50, and 100 microM. Infused RGDV decreased the accumulation of both platelets and fibrin on the collagen substrate in a dose-response manner. At the highest dose platelet and fibrin deposition after 40 min was reduced by greater than 80% (P less than 0.01). In the region of disturbed flow, RGDV (100 microM) reduced platelet deposition by 85% (P less than 0.01) but did not reduce the accumulation of fibrin (P less than 0.3). Similarly, the peptide inhibited the release of granular proteins from platelets associated with thrombus (platelet factor 4, beta-thromboglobulin; P less than 0.01), but did not prevent the appearance of fibrinopeptide A in circulating blood (P greater than 0.1). No systemic alterations in blood pressure, bleeding time, or platelet aggregation ex vivo were produced by locally infused RGDV. The antithrombotic effects of RGDV peptide disappeared within 5 min after discontinuing the infusion. In control studies infused RGEV (Arg-Gly-Glu-Val, 100 microM) showed no antithrombotic activity. Thus, RGDV selectively blocks platelet-dependent thrombus formation in vivo.